Molecular characterization of endophytic fungi-Daldinia eschscholtzii from Aloe vera plants in Bangladesh (Jahangirnagar University Journal of Biological Sciences, 2023)
Aloe vera (L.) Burm. f. is a plant of health, beauty and medicine that is widely used in Bangladesh with high demand. An experiment was performed to find out the association of endophytic fungus with Aloe vera leaves and to assess their growth behavior on different culture media, temperatures and pH. The endophytic fungus-Daldinia eschscholtzii (Ehrenb.) Rehm. was identified based on the morphological and molecular characterization using the ITS-rDNA sequence. Various solid culture media were used to assess the fungal growth, and temperature regimes i.e., 15℃, 20℃, 25℃, 30℃, 35℃ were investigated. The fungal endophyte showed maximum mycelial growth on Potato Sucrose Agar followed by Potato Dextrose Agar and Carrot Agar media. Optimum growth and development of the endophyte was recorded at temperature 25 to 35℃. We observed the effect of five different pH conditions, viz., 5, 6, 7, 8, 9 on the mycelial growth of the fungus. However, the fungal endophyte was very insensitive to the pH of the substrate. To the best of our knowledge, this is the first known occurrence of D. eschscholtzii as an endophyte in Aloe vera in Bangladesh.Jahangirnagar University J. Biol. Sci. 11(1 & 2): 1-11, 2022 (June & December)